Application of plasmonic metal nanoparticles in TiO2-SiO2 composite as an efficient solar-activated photocatalyst: A review paper - Collin Glen Joseph Anthony Joseph; Yap, Taufiq Yun Hin; Baba Musta; Mohd Sani bin Sarjadi; Elilarasi, L. (Frontiers Media S.A., 2021)
Over the last decade, interest in the utilization of solar energy for photocatalysis treatment processes has taken centre-stage. Researchers had focused on doping TiO2 with SiO2 to obtain an efficient degradation rate of various types of target pollutants both under UV and visible-light irradiation. In order to further improve this degradation effect, some researchers resorted to incorporate plasmonic metal nanoparticles such as silver and gold into the combined TiO2-SiO2 to fully optimize the TiO2-SiO2’s potential in the visible- light region. This article focuses on the challenges in utilizing TiO2 in the visible-light region, the contribution of SiO2in enhancing photocatalytic activities of the TiO2-SiO2 photocatalyst, and the ability of plasmonic metal nanoparticles (Ag and Au) to edge the TiO2-SiO2 photocatalyst toward an efficient solar photocatalyst. © 2021 Joseph, Taufiq-Yap, Musta, Sarjadi and Elilarasi.